2009
DOI: 10.4070/kcj.2009.39.12.548
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension Caused by Renal Arteriovenous Fistula

Abstract: We describe a case of secondary hypertension caused by renal arteriovenous fistula. An 8-year old girl was hospitalized with a severe headache, vomiting, and seizure. Renal angiography demonstrated multiple renal arteriovenous fistula and increased blood renin concentration in the left renal vein. Thus, left renal arteriovenous fistula and renin induced secondary hypertension were diagnosed. Her blood pressure was well controlled by medication with angiotensin converting enzyme inhibitor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Definitive treatment is required in patients who have symptomatic AVM. Patients with persistent haematuria, massive haematuria or frank AVM rupture require therapeutic intervention 8 9. As in our study the patient had persistent frank haematuria so we decided to undergo embolisation of the vessel.…”
Section: Discussionmentioning
confidence: 90%
“…Definitive treatment is required in patients who have symptomatic AVM. Patients with persistent haematuria, massive haematuria or frank AVM rupture require therapeutic intervention 8 9. As in our study the patient had persistent frank haematuria so we decided to undergo embolisation of the vessel.…”
Section: Discussionmentioning
confidence: 90%
“…No evidence in the literature currently compares medical treatment to therapeutic interventions. There are, however, reports of patients being medically managed and obtaining control of their secondary hypertension without any invasive intervention [10]. However, patients are more likely to achieve control of their hypertension with interventional therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, balloon embolization require large sheaths and embolization can occur if there is premature balloon deflation. Coil embolization techniques are now the most widely used approach to occlude AVF, because it is more convenient and is associated with less complications than balloon embolizaion 16). However, it has been reported that only five cases of ACF have been performed successfully using coil embolization 13)15)17)18).…”
Section: Discussionmentioning
confidence: 99%
“…Coil embolization techniques are now the most widely used approach to occlude AVF, because it is more convenient and is associated with less complications than balloon embolizaion. 16) However, it has been reported that only five cases of ACF have been performed successfully using coil embolization. 13) 15) 17) 18) Why is less successful coil embolizaiton of iatrogenic ACF cases seem to be first, migrated coil into coronary venous system or entering epicardial coronary arteries due to inappropriate coil size, location site and lack of ability to cannulating the distal fistula and second, maybe iatrogenic ACF underestimated.…”
Section: Discussionmentioning
confidence: 99%